Prevalence of Helicobacter pylori infection among patients attending gastroenterology endoscopy unit at Serdang Hospital - Chieng, Jin Yu; Pan, Yan; Loong, Yik Yee (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2015)
To study the prevalence of Helicobacter Pylori (H. pylori) infection, according to ethnicity, gender and endoscopic findings among the patients underwent the oesophago-gastro-duodenoscopes (OGDS) at gastroenterology endoscopy unit, Hospital Serdang, Selangor, Malaysia. The database of all whom underwent OGDS at the gastroenterology endoscopy unit, Hospital Serdang from 1stAugust 2010 to 31stJuly 2012 was collected and assessed, retrospectively. A total of 924 patients who underwent OGDS were analyzed for the H. pylori infection by using Campylobacter-like organism (CLO) test. 130 (14.07%) tested positive, and their data were further studied according to gender, ethnicity, age group, initial indication for OGDS and endoscopic finding. The prevalence rate among males was 15.15% (70/462), while it was 12.99% (60/462) among females. In terms of ethnics, H. pylori infection was commonly found among Indian and Chinese with prevalence rate of 25.13% (50/199) and 17.41% (51/293) respectively. These figures are significantly higher than the 6.01% (25/416) for Malays. The age group (31-50 years old) had the highest prevalence rate of H. Pylori infection, which is of 18.55% (41/221). No significant difference was observed among initial indications for OGDS. Erosions were the commonest finding in H. pylori positive group with rate of 51.54% (67/130). However, erosions were not uncommon in H. pylori negative group as well with the rate of 48.61% (386/794). H. pylori infection rate among Malaysians was generally low, with the highest rate in Indians, followed by Chinese and relatively low in Malays. No significant difference between the prevalence rate of H. pylori infection in male and that in female was found. Erosions were equally common in either H. pylori positive or H. pylori negative group.